2005
DOI: 10.1104/pp.105.062091
|View full text |Cite
|
Sign up to set email alerts
|

The Root Tip and Accelerating Region Suppress Elongation of the Decelerating Region without any Effects on Cell Turgor in Primary Roots of Maize under Water Stress

Abstract: To identify the region in which a root perceives a decrease in the ambient water potential and changes its elongation rate, we applied two agar blocks (1 3 1 3 1 mm 3 ) with low water potential bilaterally to primary roots of maize (Zea mays) at various positions along the root. When agar blocks with a water potential of 21.60 MPa (21.60-MPa blocks) or lower were attached to a root tip, the rate of elongation decreased. This decrease did not result from any changes in the water status of elongating cells and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 43 publications
(59 reference statements)
2
25
0
2
Order By: Relevance
“…Moreover, the synthesis of the above mentioned osmolytes as an energy dependent process which consumes a great quantity of ATP molecule, might affecting the growth (Raven 1985). On the other hand, a strong decline of cell division rate surely occurs in salt treated N. tabacum callus cell as observed in maize (Zidan et al 1990;Shimazaki et al 2005), in A. cepa (Bennici and Tani 2009) and Arabidopsis roots (West et al 2004). In regard to this last phenomenon, chromosomal aberrations (bridges, stickiness, fragmentation, exclusion, laggard and others) can not be excluded (Hossain et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the synthesis of the above mentioned osmolytes as an energy dependent process which consumes a great quantity of ATP molecule, might affecting the growth (Raven 1985). On the other hand, a strong decline of cell division rate surely occurs in salt treated N. tabacum callus cell as observed in maize (Zidan et al 1990;Shimazaki et al 2005), in A. cepa (Bennici and Tani 2009) and Arabidopsis roots (West et al 2004). In regard to this last phenomenon, chromosomal aberrations (bridges, stickiness, fragmentation, exclusion, laggard and others) can not be excluded (Hossain et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Root elongation is also inhibited under water stress, but there are two main differences between Al and drought stress: (i) under drought stress shoot growth is much more affected than root growth (reviewed by , whereas short and medium-term Al excess may strongly reduce root growth without affecting shoot growth (Kochian et al 2004;Yang et al 2009); (ii) Al toxicity reduces cell elongation along the entire elongation zone (Kollmeier et al 2000), whereas under water deficit or osmotic stress cell elongation is inhibited only in the basal and central elongation zones (definition of zones according to Ishikawa and Evans 1993), but maintained toward the root apex (Sharp et al 1988) in the distal and apical elongation zones (Shimazaki et al 2005) (Fig. 1).…”
Section: Root-growth Response Of Plants To Aluminium Toxicity and Dromentioning
confidence: 99%
“…As in the shoot model, growing tissue was seen as a distributed sink for water. However, since the publication of that theory, experimental studies have revealed that the root tip is not in equilibrium with the bathing medium (Pritchard et al, , 2000Gould et al, 2004;Shimazaki et al, 2005). Pressure probes combined with osmotic potential determinations have shown that the C of exterior root cells ranges from 20.17 to 20.6 MPa, depending on environmental conditions.…”
mentioning
confidence: 99%